Afatinib in squamous cell carcinoma of the head and neck. (12th June 2016) - Specenier, Pol; Vermorken, Jan
ABSTRACT: Introduction : Recently new data on the efficacy of afatinib in head and neck squamous cell carcinoma (HNSCC) have been published. Areas covered : We searched the literature for published and ongoing studies with afatinib in HNSCC. Phase I data and results of phase II and III studies of afatinib in HNSCC are discussed. The maximum tolerated dose (MTD) of afatinib monotherapy with continuous administration was determined at 40 or 50 mg/day, rash and diarrhea being the principal dose-limiting toxicities. The MTD was lower when combined with chemotherapy. Studies with afatinib have been conducted or are ongoing both in the recurrent or metastatic (R/M) and in the locoregionally advanced (LA) HNSCC disease setting. Expert opinion : Comparable disease control and tumor shrinkage rates were observed with cetuximab and afatinib in HNSCC progressing after platinum-containing chemotherapy. In patients with R/M- Squamous cell carcinoma of the head and neck (SCCHN) who had progressed on/after first-line platinum-based therapy, afatinib induced significantly higher disease control rate, longer progression-free survival and improved patient-reported outcome compared to methotrexate. Randomized phase III trials studying the role of adjuvant afatinib after definitive or postoperative chemoradiation in LA-HNSCC are ongoing.